2017
DOI: 10.3892/etm.2017.4656
|View full text |Cite
|
Sign up to set email alerts
|

A novel antitumor compound nobiliside D isolated from sea cucumber (Holothuria nobilis Selenka)

Abstract: Abstract. An anticancer compound, triterpene glycoside, was isolated from Holothuria nobilis Selenka. Its chemical structure and configuration were determined by two-dimensional nuclear magnetic resonance spectroscopy and electrospray ionization mass spectrometry. The novel active compound was identified as nobiliside D, with the molecular formula C 40 H 61 O 17 SNa and chemical name 3alcohol. An antitumor test was performed using xCELLigence Real-Time Cell Analysis. Nobiliside D exhibited inhibitory effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Many studies have reported that sea cucumber extract contains several compounds, including mono sulfated tritepenoid glycoside Frondoside A, disulfated glycoside Frondoside B, trisulfated glycoside Frondoside C, eicosapentaenoic acid, fucosylated chondroitin sulfate, nobiliside D, 12-methyltetradecanoic acid, sphingoid and canthaxanthin/astaxanthin, that have induced apoptosis in solid cancers, including breast, liver, renal, cervical, lung, and colorectal cancer cells [15,24,25,26]. Amidi et al reported that (Z)-2,3-diphenylacrylonitrile molecules isolated from Persian Gulf SC were identified as potential anti-cancer agents [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that sea cucumber extract contains several compounds, including mono sulfated tritepenoid glycoside Frondoside A, disulfated glycoside Frondoside B, trisulfated glycoside Frondoside C, eicosapentaenoic acid, fucosylated chondroitin sulfate, nobiliside D, 12-methyltetradecanoic acid, sphingoid and canthaxanthin/astaxanthin, that have induced apoptosis in solid cancers, including breast, liver, renal, cervical, lung, and colorectal cancer cells [15,24,25,26]. Amidi et al reported that (Z)-2,3-diphenylacrylonitrile molecules isolated from Persian Gulf SC were identified as potential anti-cancer agents [27].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining metabolites reported from echinoderms included steroidal glycosides pentacerosides A 1461 and B 1462 (Pentaceraster gracilis), 694 regulusosides S1 1463 and S2 1464 (P. regulus), 695 pentaregulosides A-G 1465-1471 (P. regulus), 696 and granulatoside C 1472 (Choriaster granulatus), 697 all isolated from starsh, as well as sea cucumbersourced triterpene glycosides nobiliside D 1473 (Holothuria nobilis), 698 stichorrenosides A-D 1474-1477 (Stichopus horrens), 699 magnumosides A 1 -A 4 , B 1 -B 4 , C 1 -C 4 1478-1489 (Neothyonidium (¼Massinium) magnum), 700,701 and fallaxosides B 1 and D 3 1490, 1491 (Cucumaria fallax). 702 Nobiliside D 1473 showed strong cytotoxicity towards a panel of six HTCLs, 698 while magnumoside C 4 1489 enhanced the antiproliferative effects of g-radiation on DLD-1 human colorectal adenocarcinoma cells. 700 Biological evaluation of carbohydrate conjugates of the sea urchin quinonoid ethylmompain identied analogues with enhanced cytotoxicity and the ability to inhibit urchin spermatozoids.…”
Section: Echinodermsmentioning
confidence: 99%
“…Triterpene glycosides of sea cucumber are known to possess a broad range of medicinal and physiological activities [ 10 , 11 ]. The medical potency of sea cucumber saponins exhibits plentiful health benefits due to their cardiovascular, ant-diabetic, hypoglycaemia, anti-oxidant, anti-asthma, anti-eczema, anti-inflammatory, anti-arthritic, anti-diabetics, cholesterol-lowering effect, immunomodulator, cytotoxic, anti-parasitic, anti-viral, antifungal [ 7 , 12 ], anticancer [ 13 , 14 ], anti-angiogenesis, anti-proliferative [ 15 ], and anti-dementia activities [ 2 ]. According to the literature, saponins also possess neuroprotective effects on the diminution of central nervous system disorders, namely Alzheimer’s disease, Huntington’s disease, Parkinson’s disease, and strokes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%